Investigation of gut microbiota in pediatric patients with peanut allergy in outpatient settings - Li, Shouming; Huang, Jingyi; Xie, Yunyun; Wang, Di; Tan, Xin; Wang, Yufan (Frontiers in Pediatrics, 2025)
ObjectiveInvestigate the diversity of the gut microbiota in children with peanut allergies and assess its association with allergic reactions. Identify potential gut microbial biomarkers for the diagnosis and treatment of peanut allergies.MethodsTwenty-nine children with peanut allergy who visited the hospital from December 2020 to December 2022 were selected as the test group (PA), and twenty-seven healthy children who underwent physical examination during the same period and tested negative for peanut IgE were selected as the control group (Ctl). The differences in gut microbiota between the two groups were compared. The study enrolled 29 children with peanut allergy (PA group) and 27 healthy children (Ctl group) from December 2020 to December 2022. The PA group was defined by a positive reaction to peanut-specific IgE tests, while the Ctl group tested negative for peanut IgE and had no history of allergies. Fecal samples were collected and genomic DNA was extracted for 16S rRNA gene sequencing to assess gut microbiota composition. Alpha diversity indices, including the sob, ace, chao, shannon, and simpson indices, were calculated to assess microbial community richness and diversity. Beta diversity was analyzed using Principal Coordinate Analysis (PCoA) and Partial Least Squares Discriminant Analysis (PLS-DA) to compare microbial community structures between the PA and Ctl groups.ResultsThe study identified significant differences in gut microbiota diversity between children with peanut allergy (PA group) and healthy controls (Ctl group). The PA group exhibited reduced alpha diversity, indicated by lower sob, ace, and chao indices (FDR ≤ 0.05), and a significantly lower Shannon index (FDR ≤ 0.01). Beta diversity analysis revealed distinct microbial community structures between the two groups. Notably, the PA group showed an increase in Proteobacteria and a decrease in Firmicutes and Bacteroidetes, with significant changes at the genus level, including lower relative abundance of Bacteroides and Faecalibacterium, and higher relative abundance of Bifidobacterium and Lactobacillus (FDR ≤ 0.05 or FDR ≤ 0.01). Correlation analysis highlighted a strong negative correlation between IgE levels and specific microbial groups, such as Alistipes and CAG-352 (FDR ≤ 0.001), and a positive correlation with Veillonella. Blood routine indicators were also found to be correlated with gut microbiota composition.ConclusionThe findings of this study provide compelling evidence that gut microbiota diversity and composition are significantly altered in children with peanut allergy. The observed shifts in microbial communities, particularly the increase in Proteobacteria and the decrease in beneficial bacteria such as Firmicutes and Bacteroidetes, underscore the potential role of the gut microbiome in the pathogenesis of peanut allergy. These results suggest that modulating the gut microbiota may be a viable therapeutic strategy for managing peanut allergy and highlight the need for further research to explore the clinical implications of these microbial changes.